The Role of Exercise on Cardiometabolic Profile and Body Composition in Youth with Type 1 Diabetes - Maria Kaza; Charalampos Tsentidis; Elpis Vlachopapadopoulou; Spyridon Karanasios; Irine-Ikbale Sakou; George Mastorakos; Kyriaki Karavanaki (MDPI AG, 2022)
Exercise has a direct positive effect on glycemic control by promoting insulin secretion from β-pancreatic islet-cells and by increasing skeletal muscle glucose uptake. The reduction in daily insulin needs and the optimization of glycemic control improves the patient's quality of life, self-esteem, mental wellness, as well as diabetes-related mobility and mortality. The aim of this study was to investigate the effect of physical activity in children and adolescents with type-1 diabetes (T1D) on diabetic control, cardiovascular, and biochemical profiles; hs-CRP; IL6; leptin; and adiponectin levels of the population under study. This is a prospective cross-sectional study that involved 80 participants (36 boys and 44 girls) with T1D, who were aged 6-21 years and who attended the Diabetes and Metabolism Clinic of the 2nd Pediatric Department, University of Athens, "P & A Kyriakou" Children's Hospital of Athens. Twenty (25%) children were above the 75th percentile regarding total levels of physical activity, while 40 (50%) and 20 (25%) were between the 25th and 75th percentile, as well as below the 25th percentile, respectively. In the group with an intermediate level of exercise, physical activity was negatively associated with the participant's family situation (traditional, single parent, grandparent, with others, or by himself/herself) (p = 0.013), ferritin (p = 0.031), lipoprotein(a) [Lp(a)] (p = 0.016), and squared leptin levels (p = 0.040). Whereas in the groups with extreme vs. no exercise there was a negative association with the number of daily glucose measurements (p = 0.047). However, in the group with non-vigorous exercise, physical activity was positively associated with high density lipoprotein-c (HDL-c) levels (p = 0.048). The findings of this study are indicative of the beneficial role of exercise on children and adolescents with T1D, which is achieved by primarily improving their cardiometabolic profile through the amelioration of lipid profile [HDL-c, Lp(a)] and leptin levels, as well as by reducing chronic systemic inflammatory response (ferritin) and ultimately decreasing the overall diabetes morbidity.